2007
DOI: 10.1302/0301-620x.89b11.19840
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of loosening of the femoral component in legacy posterior stabilised-flex total knee replacement

Abstract: We have examined the results obtained with 72 NexGen legacy posterior stabilised-flex fixed total knee replacements in 47 patients implanted by a single surgeon between March 2003 and September 2004. Aseptic loosening of the femoral component was found in 27 (38%) of the replacements at a mean follow-up of 32 months (30 to 48) and 15 knees (21%) required revision at a mean of 23 months (11 to 45). We compared the radiologically-loose and revised knees with those which had remained well-fixed to identify the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
132
6
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 59 publications
7
132
6
3
Order By: Relevance
“…Nagura et al found that deep-flexion activities generate one to 13 times larger net quadriceps moments (average five) than does walking [25]. This may increase patellofemoral joint stresses, with the potential for causing pain, excess wear, patellar fracture, and loosening [9,32]. Han et al reported a 38% prevalence of femoral component loosening in the LPS HF TKA at a mean follow-up of 2.7 years in patients engaging in weight-bearing, high flexion activities [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagura et al found that deep-flexion activities generate one to 13 times larger net quadriceps moments (average five) than does walking [25]. This may increase patellofemoral joint stresses, with the potential for causing pain, excess wear, patellar fracture, and loosening [9,32]. Han et al reported a 38% prevalence of femoral component loosening in the LPS HF TKA at a mean follow-up of 2.7 years in patients engaging in weight-bearing, high flexion activities [9].…”
Section: Discussionmentioning
confidence: 99%
“…This may increase patellofemoral joint stresses, with the potential for causing pain, excess wear, patellar fracture, and loosening [9,32]. Han et al reported a 38% prevalence of femoral component loosening in the LPS HF TKA at a mean follow-up of 2.7 years in patients engaging in weight-bearing, high flexion activities [9]. Some HF femoral components also require a larger bone resection [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A third study reported no difference in average postoperative knee flexion in 50 patients who underwent bilateral TKAs (138°for NexGen 1 LPS-Flex versus 135°for NexGen 1 LPS) [26]. To date, three of nine clinical studies suggest patients have increased postoperative flexion with highflexion prostheses [6,19,20,23,26,38,42,44,45]. One of these studies reported patients with maximum flexion greater than 135°had a better functional WOMAC Osteoarthritis Index score than patients with maximum flexion of 135°or less (17.5 versus 14.3) [45].…”
Section: Introductionmentioning
confidence: 99%
“…These high stresses may lead to pain, increased wear, fracture, and increased patellar loosening. One study of high-flexion TKAs reported a 38% rate of aseptic loosening at 32 months followup [20]. What is not known currently is how often patients will use, during daily activities, any additional safe flexion provided by the high-flexion TKA.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples in the long history of orthopaedics demonstrating that slow, gradual incorporation of new technology is advisable. It is important to remember the unforeseen consequences of certain metal-on-metal hip resurfacing and replacement designs [6], the early failure of new bone cement formulations [1,4], and the unpredicted failures of even fairly minor modifications to successful products, including certain ''high flex'' femoral component designs [3]. Orthopaedics certainly is not alone in having suffered such repercussions of untested new technology-novel pacemakers [2] and cochlear implants [5] are just two examples that come to mind from outside our specialty.…”
mentioning
confidence: 99%